Functional reorganization of the auditory pathways (or lack thereof) in callosal agenesis is predicted by monaural sound localization performance - Paiement, Philippe; Champoux, François; Bacon, Benoit A.; Lassonde, Maryse; Mensour, Boualem; Leroux, Jean-Maxime; Lepore, Franco (Neuropsychologia, 2010)
Neuroimaging studies show that permanent peripheral lesions such as unilateral deafness cause functional reorganization in the auditory pathways. However, functional reorganization of the auditory pathways as a result of higher-level damage or abnormalities remains poorly investigated. A relatively recent behavioural study points to functional changes in the auditory pathways in some, but interestingly not in all, of the acallosal individuals that were tested. The present study uses fMRI to investigate auditory activities in both cerebral hemispheres in those same acallosal subjects in order to directly investigate the contributions of ipsilateral and contralateral functional pathways reorganization. Predictions were made that functional reorganization could be predicted from behavioural performance. As reported previously in a number of neuroimaging studies, results showed that in neurologically intact subjects, binaural stimulation induced balanced activities between both hemispheres, while monaural stimulation induced strong contralateral activities and weak ipsilateral activities. In accordance with behavioural predictions, some acallosal subjects showed patterns of auditory cortical activities that were similar to those observed in neurologically intact subjects while others showed functional reorganization of the auditory pathways. Essentially they showed a significant increase and a significant decrease of neural activities in the contralateral and/or ipsilateral pathways, respectively. These findings indicate that at least in some acallosal subjects, functional reorganization inside the auditory pathways does contribute to compensate for the absence of the corpus callosum.